2018
DOI: 10.1149/2.0661803jes
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Electrodeposition of Layer by Layer Architectural Si-Graphene Nanocomposite Anode of Lithium Ion Battery with Enhanced Cycle Performance

Abstract: One step electrodeposition is applied to prepare Si-Graphene (SiG) composites from Graphene(G)-SiCl 4 - [BMP]tf 2 N ionic liquid. The SiG composites have shown an alternate layer-structure of Si and graphene caused by alternate processes of Si reduction and graphene adsorption on the electrode, which is confirmed by the regular current pulsation in the chronoamperometric curves during the whole electrodeposition process. The SEM and TEM morphologies indicate that each layer is about 120 nm thickness for the Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…Moreover, the specific capacity of SiCu-2.1 is 1038.2 mAh/g after 750 cycles. Compared with our previous work, 37 bare Si electrode delivers a relatively lower capacity of 970 mAh/g at the end of the 200th cycle. The results indicate that the introduction of Cu promotes Li + and electron transfer to enhance the cycling performance of Si.…”
Section: Resultscontrasting
confidence: 70%
See 1 more Smart Citation
“…Moreover, the specific capacity of SiCu-2.1 is 1038.2 mAh/g after 750 cycles. Compared with our previous work, 37 bare Si electrode delivers a relatively lower capacity of 970 mAh/g at the end of the 200th cycle. The results indicate that the introduction of Cu promotes Li + and electron transfer to enhance the cycling performance of Si.…”
Section: Resultscontrasting
confidence: 70%
“…−0.65 V to about −1.5 V and peaking at −1.2 V presents the reduction of Si 4+ to Si 2+ , then the B2 step peaking at −1.65 V was the reduction reaction of Si 2+ to Si 0 on Cu substrate, and B3 with the reduction current appearing at ca. −1.8 V corresponds the Si deposition process, which was caused by the reduction of Si 4+ to Si 0 element on the Si film. The above different potentials of Si 4+ to Si are attributed to different working electrodes. The reduction potential of Si 4+ to Si shifts to a more positive value on the Cu electrode due to underpotential electrodeposition, while the reduction potential of Si 4+ to Si remains relatively negative on the Si electrode.…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, the intrinsic interfacial interactions between BG could be totally shielded, leading to the vertical orientation of BG sheets with relatively independent units on electrodes. 34,[36][37][38][39] It is well known that, larger interactions between metals and functional groups of surfaces can increase the dispersive character of IMBs atoms. During this deposition process, dispersive Fe-Co-Ni-B nanoparticles were in situ nucleated and grown on the functional groups of BVG surface, leading to the formation of Fe-Co-Ni-B/BVG composite.…”
Section: Resultsmentioning
confidence: 99%
“…We deduce that, during the simultaneous electrodeposition of the two components, each NRGO sheet was surrounded by AuCl 4 homogeneously and therefore NRGO would be entrained during the AuNPs deposition at around −0.25 V, and meanwhile the NRGO sheets that have various functional groups provided anchor sites for nucleation and growth of AuNPs at the NRGO surfaces. AuNPs would also be entrained during the NRGO deposition at around −1.2 V. 31,32,35 The formation of smaller AuNPs may be ascribed to the nitrogen atoms, which are homogeneously doped into the RGO by urea, that induce new nucleation and growth of Au atoms, leading to the formation of smaller AuNPs. This suggested that the AuNPs/NVRGO composite possessed the largest specific surface area.…”
Section: Morphology and Surface Chemistry Of Nitrogen−doped Graphenementioning
confidence: 99%